Anaerobic Fungi: A Potential Source of Biological H2 in the Oceanic Crust - Ivarsson, Magnus; Schnürer, Anna; Bengtson, Stefan; Neubeck, Anna (Frontiers in Microbiology, 2016)
The recent recognition of fungi in the oceanic igneous crust challenges the understanding of this environment as being exclusively prokaryotic and forces reconsiderations of the ecology of the deep biosphere. Anoxic provinces in the igneous crust are abundant and increase with age and depth of the crust. The presence of anaerobic fungi in deep-sea sediments and on the seafloor introduces a type of organism with attributes of geobiological significance not previously accounted for. Anaerobic fungi are best known from the rumen of herbivores where they produce molecular hydrogen, which in turn stimulates the growth of methanogens. The symbiotic cooperation between anaerobic fungi and methanogens in the rumen enhance the metabolic rate and growth of both. Methanogens and other hydrogen-consuming anaerobic archaea are known from subseafloor basalt; however, the abiotic production of hydrogen is questioned to be sufficient to support such communities. Alternatively, biologically produced hydrogen could serve as a continuous source. Here we propose anaerobic fungi as a source of bioavailable hydrogen in the oceanic crust, and a close interplay between anaerobic fungi and hydrogen-driven prokaryotes.